2015
DOI: 10.1097/ta.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation and procoagulant microparticle profiles after acute trauma

Abstract: Objective The two sides of Trauma Induced Coagulopathy (TIC), the hypo- and the hyper- coagulable states, are poorly understood. To identify potential mechanisms for venous thromboembolism and bleeding after acute trauma, we estimated changes in circulating procoagulant MPs and thrombin activity during hospitalization for trauma. Methods Whole blood was collected by venipuncture into 3.2% trisodium citrate at 0, 6, 12, 24 and 72 hours after injury, and discharge. Platelet poor plasma was harvested and stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 25 publications
5
51
1
1
Order By: Relevance
“…Various cell-derived microparticles have been detected during the acute phase of severe trauma [27][28][29][30][31][32]. Plateletderived microparticles are well-known pro-coagulants in the acute phase of trauma [27][28][29].…”
Section: Coagulation Activation-induced Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various cell-derived microparticles have been detected during the acute phase of severe trauma [27][28][29][30][31][32]. Plateletderived microparticles are well-known pro-coagulants in the acute phase of trauma [27][28][29].…”
Section: Coagulation Activation-induced Consumptionmentioning
confidence: 99%
“…Plateletderived microparticles are well-known pro-coagulants in the acute phase of trauma [27][28][29]. Furthermore, leukocyte-, erythrocyte-, and endothelial cell-derived microparticles are also released into the systemic circulation in the acute phase of trauma (29,30).…”
Section: Coagulation Activation-induced Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 However, a recent prospective study in acute trauma did not show any changes in microparticle levels over time. 67 There is uncertainty regarding their role in trauma and hemostasis and the robustness of quantitative and qualitative assays may need addressing before their role in trauma coagulopathy can be elucidated.…”
Section: Platelet Microparticlesmentioning
confidence: 99%
“…The PROMMT study demonstrated an association between decreased levels of PMPs and poor clot strength, increased blood product requirements and mortality in coagulopathic trauma patients (149). An alternate study demonstrated no significant difference in microparticle concentration with time in trauma patients (150), while a third study reported elevated PMPs in trauma patients at hospital admission that were implicated in the development of post injury multi-organ failure (151). Alterations in PMP levels may be a separate component of platelet dysfunction developing independently to impaired aggregation capacity, and may play an important part in the haemostatic and inflammatory responses to trauma.…”
Section: Role Of Platelet Function and Microparticlesmentioning
confidence: 99%